Personal Pronoun in Japanese Based on Gender (Structure and Semantic Study) - Syahrial, Syahrial (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
This research analyzed the personal pronouns of Japanese from structure and semantics based on gender. This research useddescriptive method. To discuss the personal pronoun, the theories used include the theory of Lyons (1997), Samsuri (1980), Djajasudarma (1993), Moeliono, et al. (1993), Alwi, et al. (1998), Quirck, et al. (1985), Keraf (1990), Bambang Kaswanti (1983). while For pronouns, used the theory of Oya (1992), Tomita (1993), Kindaichi (1993). The theory used for gender research was the theory of Tsujimura (1995). The results of this Research shows that the personal pronouns of Japanese are different between The speaker and the listener or addresser and addresseeboth male and female and as well as neutral. The conclusion of this study is that based on gender, personal pronoun in Japanese is different. The differences come between the greeters and the greeted or speaker and his/her partners on male and female basis